Surgical treatment of pulmonary sequestration in adults and children: long-term results. (16th April 2020) - Trabalza Marinucci, Beatrice; Maurizi, Giulio; Vanni, Camilla; Cardillo, Giuseppe; Poggi, Camilla; Pardi, Valerio; Inserra, Alessandro; Rendina, Erino A
Abstract: OBJECTIVES: Few experiences comparing paediatric and adult patients treated for pulmonary sequestration (PS) have been reported. Surgical treatment is considered the best choice, but the time of surgery is still controversial. We present our experience in this setting, comparing characteristics, histological results and outcome of paediatric and adult patients undergoing PS resection. METHODS: Between 1998 and 2017, a total of 74 patients underwent lobectomy or sublobar resection for PS. Sixty patients were children (group A: ≤16 years old) and 14 were adults (group B: >16 years old). Preoperative diagnosis was radiological. PS was intralobar (42 cases) and extralobar (32 cases). The operation was a muscle-sparing lateral thoracotomy or video-assisted thoracoscopic surgery. Preoperative characteristics, histological results and short-/long-term results of the 2 groups were retrospectively analysed and compared. RESULTS: Thirty-seven percent of the patients in group A presented with respiratory symptoms and 79% in group B ( P  = 0.44). Most symptomatic patients were treated with a lobectomy. In group A, 2 patients (3%) had a malignant transformation of the lesion. Patients with a prenatal diagnosis treated after the age of 1 year became more symptomatic than those operated on before the age of 1 year (57% vs 23%; P  = 0.08). No differences were found in postoperative complications. Long-term stable remission of respiratory symptoms was obtained in 91% of patients in group A and 100% in group B. Adulthood ( P  = 0.03) and the association with congenital cystic adenomatoid malformation ( P  = 0.03) were negative prognostic factors for the development of respiratory symptoms. CONCLUSIONS: Surgical treatment of PS is safe and feasible. Despite the small number of patients included, study results indicated that an early operation during childhood may prevent the subsequent development of respiratory symptoms. Surgical treatment is also recommended to prevent the rare transformation into malignancy.